The Idea of Human Rights: From the Ancient World to the Digital Age - Aznagulova, Guzel; Kashevarova, Yulia; Pashentsev, Dmitry (Տիգրան Մեծ)
The purpose of the article is to identify the features of the development of the idea of human rights, starting from the Ancient World, and on this basis to show its significance in the digital age. To achieve this goal, the conceptual foundations of the idea of human rights and their reflection in political and legal thought at different stages of the evolution of society and science are analysed. The subject of the study was the concept of human rights. The study was conducted on the basis of post-non-classical scientific methodology, including constructivism. The formal-legal and comparative-historical methods are also used. According to the results of the study, it is concluded that in the conditions of modern technological development, digitalisation is becoming a challenge to the idea of human rights, a threat to individual freedom, and therefore it is necessary to develop and implement new legal mechanisms that would guarantee the full implementation of fundamental rights and freedoms, provide the necessary balance between individual freedom and public security. In this context, the legal consolidation and practical implementation of the principle of formal equality become important.
Keywords: Digital technologies; Philosophy of Law